2010
DOI: 10.1515/bc.2010.026
|View full text |Cite
|
Sign up to set email alerts
|

KLK5 gene expression is severely upregulated in androgen-independent prostate cancer cells after treatment with the chemotherapeutic agents docetaxel and mitoxantrone

Abstract: Kallikrein-related peptidases (KLKs), including KLK5, have been proposed as promising biomarkers for prostate cancer diagnosis and prognosis. In the present study, we report that distinct augmentations (up to 6.4-fold) of KLK5 mRNA expressional levels, calculated via quantitative real-time PCR, occur after treatment of DU145 cells with appropriate concentrations, determined by the MTT method, of docetaxel and mitoxantrone. Our data reveal the endogenous need of prostate cancer cells for modified KLK5 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…KLK5 mRNA expression was also dysregulated in DU145 prostate cancer cells after administration of the antineoplastic agents docetaxel and mitoxantrone. The same study postulated that the expression profi le of KLK5 could serve as a putative biomarker for monitoring the treatment response in hormone refractory prostate cancer patients (152) . According to our unpublished results, modulations of KLK5 and KLK14 mRNA levels were observed in BT-20 breast cancer cells during their apoptosis, induced by their exposure to chemotherapeutic drugs, such as epirubicin, docetaxel, and methotrexate.…”
Section: Klks In Personalized Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…KLK5 mRNA expression was also dysregulated in DU145 prostate cancer cells after administration of the antineoplastic agents docetaxel and mitoxantrone. The same study postulated that the expression profi le of KLK5 could serve as a putative biomarker for monitoring the treatment response in hormone refractory prostate cancer patients (152) . According to our unpublished results, modulations of KLK5 and KLK14 mRNA levels were observed in BT-20 breast cancer cells during their apoptosis, induced by their exposure to chemotherapeutic drugs, such as epirubicin, docetaxel, and methotrexate.…”
Section: Klks In Personalized Medicinementioning
confidence: 99%
“…For instance, the combined molecular profi le of the KLK5 and KLK11 genes has been proposed as a new potential molecular biomarker predicting treatment response of prostate cancer (152,153) . In more detail, treatment of PC-3 prostate cancer cells with mitoxantrone, etoposide, doxorubicin and/or carboplatin was shown to induce distinct alterations in the mRNA expression of KLK5 and KLK11 (153) .…”
Section: Klks In Personalized Medicinementioning
confidence: 99%
“…In contrast to the abovementioned family members, KLK5 (Yousef et al , 2002b ;Korbakis et al , 2009 ) and KLK11 (Nakamura et al , 2003b ;Bi et al , 2010 ) expression levels are correlated with early disease stages and low Gleason scores, highlighting the favorable prognostic nature for patients. Finally, treatment of the androgen-independent prostate cancer cell lines, PC3 and DU145, with broadly used chemotherapeutic agents alters KLK5 expression, indicating its promising value for monitoring of patients ' response to chemotherapy (Thomadaki et al , 2009 ;Mavridis et al , 2010b ).…”
Section: Clinical Relevance Of Kallikrein-related Peptidases For Cancmentioning
confidence: 99%
“…Increasing KLK2 serum levels have been associated with residual tumors and biochemical recurrence after the local treatment of patients, designating in this way the presence of a clinical relapse (Ulmert et al, 2009). Additionally, recent promising studies reported severe overexpression of KLK5 gene transcription levels, after treatment of the androgen-independent prostate cancer cell lines PC3 and DU145 with various and broadly used, in clinical practice, chemotherapeutic agents (Thomadaki et al, 2009;Mavridis et al, 2010b). The fact that modulation of the expression levels of these genes were triggered by the presence of anticancer compounds demonstrates the promising clinical value of these family members in the field of monitoring patients' response to chemotherapy in androgenindependent PCa.…”
Section: Klks As Cancer Monitoring Biomarkersmentioning
confidence: 97%